The Effect of Gender Differences and Lack of Administrative Support on Poor Employee Performance with the Mediation of Disputes between Employees of a Distributor Company - Vincent, Tomi; Dini, Yuli Indah Fajar; Mon, Muhammad Donal (Universitas Proklamasi 45, 2025)
This study examines the impact of gender discrimination, inadequate administrative support, and hostility among employees on the subpar job performance of distributor companies in Batam City. According to BPS data, there are 2,153 distributor companies in Batam City, employing a total of 259,749 employees. The sample of this study was obtained from 382 respondents working in distributor companies who filled out questionnaires online via Google Forms. The processed data came from 365 respondents, with 54.25 percent of the respondents being male. This study uses quantitative data analysis techniques and descriptive quantitative research. The data was collected using survey techniques or questionnaires and processed using Partial Least Square (PLS). Results of this study showed that Gender Discrimination and Lack of Administrative to Person-Related Hostility have a positive and significant effect (H1) and (H2). Gender Discrimination, Lack of Administrative Support, and Person-related hostility to Poor Job Performance have a positive and significant effect (H3), (H4), and (H5). Then, Gender Discrimination and Lack of Administrative Support have a significant indirect impact on Poor job performance and are mediated by person-related hostility (H6) & (H7). So, this study consists of 7 hypotheses, directly from H1 to H5 and indirectly from H6 to H7.